Recent advances in ginseng as cancer therapeutics: a functional and mechanistic overview. Issue 2 (27th October 2014) - Wong, Alice S. T.; Che, Chi-Ming; Leung, Kar-Wah
Abstract : This review covers recent research advances in elucidating the anti-cancer mechanisms of ginsenosides and their potential clinical applications. Abstract : Covering: 2000 to 2014 Cancer is one of the leading causes of death worldwide. Ginseng, a key ingredient in traditional Chinese medicine, shows great promise as a new treatment option. As listed by the U.S. National Institutes of Health as a complementary and alternative medicine, its anti-cancer functions are being increasingly recognized. This review covers the mechanisms of action of ginsenosides and their metabolites, which can modulate signaling pathways associated with inflammation, oxidative stress, angiogenesis, metastasis, and stem/progenitor-like properties of cancer cells. The emerging use of structurally modified ginsenosides and recent clinical studies on the use of ginseng either alone or in combination with other herbs or Western medicines which are exploited as novel therapeutic strategies will also be explored.